Effects of chitin synthesis inhibitor treatment on Lepeophtheirus salmonis (Copepoda, Caligidae) larvae - Hardardottir, Hulda; Male, Rune; Nilsen, Frank; Dalvin, Sussie (PLOS ONE, 2019)
The salmon louse (Lepeophtheirus salmonis) is an ectoparasite infecting Atlantic salmon (Salmo salar), which causes substantial problems to the salmon aquaculture and threatens wild salmon. Chitin synthesis inhibitors (CSIs) are used to control L. salmonis in aquaculture. CSIs act by interfering with chitin formation and molting. In the present study, we investigated the action of four CSIs: diflubenzuron (DFB), hexaflumuron (HX), lufenuron (LF), and teflubenzuron (TFB) on larval molt. As the mode of action of CSIs remains unknown, we selected key enzymes in chitin metabolism and investigated if CSI treatment influenced the transcriptional level of these genes. All four CSIs interfered with the nauplius II molt to copepodids in a dose-dependent manner. The EC50 values were 93.2 nM for diflubenzuron, 1.2 nM for hexaflumuron, 22.4 nM for lufenuron, and 11.7 nM for teflubenzuron. Of the investigated genes, only the transcriptional level of L. salmonis chitin synthase 1 decreased significantly in hexaflumuron and diflubenzuron-treated larvae. All the tested CSIs affected the molt of nauplius II L. salmonis larvae but at different concentrations. The larvae were most sensitive to hexaflumuron and less sensitive to diflubenzuron. None of the CSIs applied had a strong impact on the transcriptional level of chitin synthesis or chitinases genes in L. salmonis. Further research is necessary to get more knowledge of the nature of the inhibition of CSI and may require methods such as studies of protein structure and enzymological studies. publishedVersion